2018
DOI: 10.15331/jdsm.6916
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Assessment of Maximum Protrusion in Patients Wearing a Mandibular Advancement Device

Abstract: Study Objectives: Obstructive sleep apnea (OSA) is a sleep-related disorder with high prevalence in our society. The gold standard for the treatment of sleep apnea is continuous positive airway pressure (CPAP). Given the low adherence rate of patients on CPAP treatment, interest has turned toward dental appliances, commonly called mandibular advancement devices (MAD). The aim of this study was to determine whether patients' maximum protrusion could be increased after wearing a MAD for 3 months, such that patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…A study determining the pressure pain thresholds (PPTs) of masticatory and neck muscles change after the application of MAD in patients with OSA showed no significant difference in the physiological functions of the masticatory muscle and neck muscles after 6 months of MAD treatment 40 . Similar to our study findings, another study also reported no greater changes in mandibular movements compared to control group after wearing MAD 41 . However, in our study changes in mandibular movement were evaluated using EMG.…”
Section: Discussionsupporting
confidence: 81%
“…A study determining the pressure pain thresholds (PPTs) of masticatory and neck muscles change after the application of MAD in patients with OSA showed no significant difference in the physiological functions of the masticatory muscle and neck muscles after 6 months of MAD treatment 40 . Similar to our study findings, another study also reported no greater changes in mandibular movements compared to control group after wearing MAD 41 . However, in our study changes in mandibular movement were evaluated using EMG.…”
Section: Discussionsupporting
confidence: 81%
“…Although the titration procedure relies on the capacity of antero-posterior mandibular excursion, few studies have investigated the potential changes in the antero-posterior mandibular movement due to MAD therapy with conflicting outcomes [ 17 , 18 , 19 , 20 , 21 , 22 ]. No difference in mandibular protrusion capacity was found at the 2-year follow-up in a prospective cohort study investigating the craniomandibular status and function in patients with habitual snoring and OSA after nocturnal treatment with the MAD [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of previous studies have not consistently indicated the method of mandibular protrusion measurement [ 17 , 18 , 19 , 20 , 21 , 22 ]. The study by Tegelberg et al [ 21 ] reported that the mandibular range of motion was measured with a steel ruler to the nearest millimeter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study explored whether patients' maximum protrusion could be increased after wearing a MAD for 3 months, such that individuals with weak protrusion (who could at first be ineligible for effective treatment) could become candidates for the therapy. 299 The treatment group consisted of 30 patients with PSG-diagnosed OSA; 30 healthy participants without OSA were matched controls. MAD was worn for 90 days while the control group received no treatment.…”
Section: Oral Appliance Therapymentioning
confidence: 99%